Essential Oil Composition of Different Accessions of Ginger Collected from Northeast Region of India. Issue 6 (2nd November 2018) - Begum, Twahira; Pandey, Sudin Kumar; Borah, Angana; Paw, Manabi; Lal, Mohan
Abstract: Zingiber officinale Roscoe, which belongs to the Zingiberaceae family, is a herbaceous perennial plant. The plant has been used since ancient time traditionally as a spice and as a natural remedy for cough, cold and asthma etc. The various chemical constituents of ginger are responsible for the multiple medicinal properties. Although northeast India is a biodiversity hotspot but so far only morphological data and oil yield has been studied. Very less work has been done on the chemical composition of ginger essential oil from the northeast region of India. In this study sixty germplasm were planted in randomized block design at the experimental farm CSIR-NEIST, Jorhat, Assam (India) during the year 2017-18. After harvesting, essential oil was isolated from the rhizome of each line and replications and average values were taken for measurement of the essential oil yield. Essential oil was analyzed through GC and GC/MS. The study revealed that the major constituent of ginger essential oil was geraniol followed by z-citral, eucalyptol, camphene and other minor constituents were α-pinene, β-myrcene, linalool, e-citral, neryl acetate, α-zingiberene, curcumene, β-sesquiphellandrene, α-amorphene, farnesene, elemol and β-bisbolene. Based on the activities of its chemical constituents, ginger essential oil can be used in various novel medicinal and phytopharmaceutical application.